Speaking Skills Problems Encountered By Non-Native Arabic Learners At Universities In Northeast China - Gu, Bingxin; Muin Ismail, Wail (Ijaz Arabi Journal of Arabic Learning, 2024)
Speaking skills are critical in second language acquisition. This study investigates the most common speaking skills problems among non-native Arabic learners in universities in Northeast China and the differences between speaking skills problems based on gender and academic level. A quantitative research design was adopted. It used the questionnaire to collect data. The sample of this study included 104 Chinese students who learn Arabic from two universities in Northeast China. The results indicate that the most common problems with Arabic speaking skills are a lack of vocabulary, opportunities to meet native Arabic speakers, fear of mistakes, teacher-centered classes, and the teacher using too many students’ native languages in the classroom. Besides that, the results show no statistically significant difference in Arabic speaking skills problems based on gender. However, the findings show statistically significant differences in Arabic speaking skills problems based on the academic level. The learners of the second year have more Arabic speaking skills problems than the learners of the first year, and the learners of the third year also have more Arabic speaking skills problems than the learners of the first year. According to the findings, the study suggests recommendations for Arabic learners, instructors, and policymakers in universities in non-Muslim gathering areas in Northeast China.